STRATEGIC PLANNING OF INFORMATION SYSTEMS IN PT KAYU LAPIS INDONESIA - Muhammad Jibril; Zulrahmadi (JURNAL PERANGKAT LUNAK, 2023)
PT Kayu Lapis Indonesia is a leading company with more than four decades of experience in the field of sustainable forest management with an integrated timber industry that already apply information systems management. Existing information systems developed by IT departments that exist in the company. Currently the company has a system of information that has been developed by internal parties for the operation of corporate transactions, such as for logistic and finance needs. But there has been no support system for the other divisions. Such a system capable of providing information related to forest management such as land clearing, seeding, harvesting, and mapping of forests managed by the company. One problem that often arises in the field that such a report for monitoring the level of production, the number of trees that have been felled in the day, diameter, volume, and others associated with production activities to be slower due to the manual recording. So we can say that the use of IS / IT within the company is not optimal. According Manuputty and Wijaaya (2013) that the use of the IS / IT strategic planning needed to be optimal information systems. It is therefore necessary to make a planning strategy for the use of information systems / IT becomes more optimal to support or improve the performance of the company